SAR image analysis : a computational statistics approach : with R code, data, and applications /: a computational statistics approach : with R code, data, and applications. (2022) - Frery, Alejandro C; Wu, Jie, 1985-; Gómez, Luis (Gómez Déniz)
No abstract available